Incidence and Predictors of Anal Incontinence After Obstetric Anal Sphincter Injury in Primiparous Women. Issue 4 (July 2015) - Richter, Holly E.; Nager, Charles W.; Burgio, Kathryn L.; Whitworth, Ryan; Weidner, Alison C.; Schaffer, Joseph; Zyczynski, Halina M.; Norton, Peggy; Jelovsek, John Eric; Meikle, Susan F.; Spino, Cathie; Gantz, Marie; et al.
Abstract : Objective: This study aimed to describe the incidence of fecal incontinence (FI) at 6, 12, and 24 weeks postpartum; anal incontinence (AI) and fecal urgency at 24 weeks; and identify predictors of AI in women with obstetric anal sphincter injury (OASI). Methods: Primiparous women sustaining OASIs were identified at 8 clinical sites. Third-degree OASIs were characterized using World Health Organization criteria, 3a (<50%) or 3b (>50%) tear through the sphincter. Fecal incontinence was defined as leakage of liquid/solid stool and/or mucus in the past month; AI was defined as leakage of liquid/solid stool and/or mucus and/or gas in the past month and was assessed at 6, 12, and 24 weeks postpartum using the Fecal Incontinence Severity Index. Logistic regression identified variables associated with AI. Results: Three hundred forty-three women participated: 297 subjects sustained a third-degree OASI, 168 type 3a, 98 type 3b and 31 indeterminant; 45 had a fourth-degree OASI. Overall FI incidence at 6, 12, and 24 weeks was 7% [23/326; 95% confidence interval (CI), 4%–10%], 4% (6/145; 95% CI, 2%–9%), and 9% (13/138; 95% CI, 5%–16%), respectively. At 24 weeks, AI incidence was 24% (95% CI, 17%–32%) and fecal urgency 21% (95% CI, 15%–29%). No significant differences in FI and AI rates were noted by third-degree type or between groups with third and fourth OASI. Flatal incontinence was greater in women sustaining a fourth-degree tear (35% vs 16%, P = 0.04). White race (adjusted odds ratio, 4.64; 95% CI, 1.35–16.02) and shorter duration of second stage (adjusted odds ratio, 1.47 per 30 minute decrease; 95% CI, 1.12–1.92) were associated with AI at 24 weeks. Conclusions: Overall 24-week incidence of FI is 9% (95% CI, 5%–16%) and AI is 24% (95% CI, 17%–32%). In women with OASI, white race and shorter second-stage labor were associated with postpartum AI. Clinical Trial Registration: NCT01166399 (http://clinicaltrials.gov ) Abstract : Obstetric anal sphincter injuries are associated with incident anal incontinence (AI) symptoms with little difference in fecal incontinence (FI) symptoms between World Health Organization (WHO) 3a and 3b laceration subtypes.